The Fragility Paradox: Re-evaluating Gen Z’s Mental Health Crisis as a Radical Shift in Leadership Intelligence - Juni Hartiwi; Ajeng Ninda Uminar; Liah Rosdiani Nasution (Indonesian Journal of Education and Youth Development, 2025)
The integration of Generation Z into the global workforce, projected to comprise 27% of labor by 2025, coincides with unprecedented rates of reported anxiety, depression, and burnout among this cohort. Prevailing management narratives often pathologize these traits as fragility or a lack of resilience, creating friction with traditional command-and-control leadership models. This integrative literature review challenges that deficit-based perspective by synthesizing scholarship from clinical psychology, management studies, and sociology to reframe Gen Z’s hypersensitivity as a form of high-level adaptive intelligence. Through the lens of Sensory Processing Sensitivity (SPS), the research argues that Gen Z’s emotional reactivity functions as high-fidelity signal detection, enabling the early identification of toxic dynamics, ethical lapses, and systemic risks that stoic leadership models overlook. The findings suggest that Gen Z’s deployment of clinical language reflects advanced emotional literacy rather than victimhood, and their eco-anxiety indicates a capacity for systemic consequence analysis essential for sustainable governance. The study concludes that the corporate sector is undergoing a necessary evolution from Stoic to Permeable leadership, where the very traits labeled as weaknesses are actually critical assets for navigating the ethical complexities of the modern world.